Fungal and Bacterial Co-Bioaugmentation of a Pesticide-Degrading Biomixture: Pesticide Removal and Community Structure Variations during Different Treatments - Castro Gutiérrez, Víctor Manuel (2021)
Biopurification systems (BPS) are employed for the treatment of pesticide-containing wastewaters. In this work, a biomixture (active core of BPS) complemented by the addition of the fungus Trametes versicolor was evaluated for the elimination of a mixture of pesticides under different treatment conditions. The biomixture achieved high removal of all the pesticides assayed after 16 d: atrazine (68.4%, t1/2: 9.6 d), carbendazim (96.7%, t1/2: 3.6 d), carbofuran (98.7%, t1/2: 3.1 d) and metalaxyl (96.7%, t1/2: 3.8 d). Variations in the treatment conditions including addition of the antibiotic oxytetracycline and co-bioaugmentation with a bacterial consortium did not significantly affect the removal performance of the biomixture. Bacterial and fungal community profiles determined by DGGE analyses revealed changes that responded to biomixture aging, and not to antibiotic or pesticide addition. The proposed biomixture exhibits very efficient elimination during simultaneous pesticide application; moreover, the matrix is highly stable during stressful conditions such as the co-application of antibiotics of agricultural use.